2021
DOI: 10.1038/s41598-021-92768-x
|View full text |Cite
|
Sign up to set email alerts
|

A specific phase of transcranial alternating current stimulation at the β frequency boosts repetitive paired-pulse TMS-induced plasticity

Abstract: Transcranial alternating current stimulation (tACS) at 20 Hz (β) has been shown to modulate motor evoked potentials (MEPs) when paired with transcranial magnetic stimulation (TMS) in a phase-dependent manner. Repetitive paired-pulse TMS (rPPS) with I-wave periodicity (1.5 ms) induced short-lived facilitation of MEPs. We hypothesized that tACS would modulate the facilitatory effects of rPPS in a frequency- and phase-dependent manner. To test our hypothesis, we investigated the effects of combined tACS and rPPS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Thus, we assumed that β-tACS synchronized with iTBS might reveal facilitatory effects beyond what is seen after M1 iTBS. Indeed, we recently found that the facilitatory after-effects of rPPS over M1 were more pronounced with β-ACS when the TMS pulses were synchronized to the peak phase but not the trough phase ( Nakazono et al, 2021 ). Conversely, α-tACS did not significantly modulate the effects of rPPS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we assumed that β-tACS synchronized with iTBS might reveal facilitatory effects beyond what is seen after M1 iTBS. Indeed, we recently found that the facilitatory after-effects of rPPS over M1 were more pronounced with β-ACS when the TMS pulses were synchronized to the peak phase but not the trough phase ( Nakazono et al, 2021 ). Conversely, α-tACS did not significantly modulate the effects of rPPS.…”
Section: Discussionmentioning
confidence: 99%
“…tACS was delivered using a battery-driven current stimulator (DC Stimulator-Plus, NeuroConn GmbH, Ilmenau, Germany) with an intensity of 1 mA. The electrode size, position, and current intensity were chosen based on previous studies ( Feurra et al, 2011 ; Helfrich et al, 2014 ; Guerra et al, 2016 ; Nakazono et al, 2016 , 2021 ). The tACS duration was 260 s, and the stimulation began 60 s before iTBS onset and lasted until iTBS offset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcranial alternating current stimulation can entrain brain oscillations and modulate brain functions in a frequency-dependent manner (Herrmann et al, 2013;Nakazono et al, 2020;Vogeti et al, 2022). Phase-dependent effects of tACS have also been found in motor (Goldsworthy et al, 2016;Guerra et al, 2016;Nakazono et al, 2016Nakazono et al, , 2021Schilberg et al, 2018;Ogata et al, 2021), auditory (Neuling et al, 2012;Riecke et al, 2015), and visual function (Helfrich et al, 2014). In the locomotor system, tACS at the gait frequency over the cerebellum synchronized the natural walking rhythm (Koganemaru et al, 2020).…”
Section: The Effects Of "Alternating Current Stimulation"mentioning
confidence: 99%